2007
DOI: 10.1001/jama.297.8.842
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality in Randomized Trials of Antioxidant Supplements for Primary and Secondary Prevention

Abstract: XIDATIVE STRESS IS IMPLIcated in most human diseases. 1,2 Antioxidants may decrease the oxidative damage and its alleged harmful effects. [3][4][5][6] Many people are taking antioxidant supplements, believing to improve their health and prevent diseases. [7][8][9][10] Whether antioxidant supplements are beneficial or harmful is uncertain. [11][12][13][14][15] Many primary or secondary prevention trials of antioxidant supplements have been conducted to prevent several diseases.We found that antioxidant suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
1,194
6
67

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,041 publications
(1,297 citation statements)
references
References 130 publications
30
1,194
6
67
Order By: Relevance
“…Akbaraly et al (77) RCT have found that Se supplementation tends to reduce mortality Bjelakovic et al (78) Thyroid effects The iodothyronine deiodinases that produce the active form of thyroid hormone are selenoenzymes, while the antioxidant selenoenzyme GPx is required for the protection of the thyroid from the H 2 O 2 produced there Arthur & Beckett (79) Severe Se deficiency occurs in the endemic goitre belt of north Zaire, which together with iodine deficiency gives rise to myxoedematous cretinism Vanderpas et al (80) An inverse association has been found between Se status and thyroid volume, thyroid tissue damage and goitre in French women Derumeaux et al (81) In RCT in patients with thyroid peroxidase antibodies or autoimmune thyroiditis Se supplementation decreases inflammation and thyroid antibody concentrations and prevents postpartum hypothyroidism Summarised in Rayman (9) GPx, glutathione peroxidise; NHANES III, Third National Health and Nutrition Examination Survey; RCT, randomised controlled trials.…”
Section: Antiviral Effects and Hivmentioning
confidence: 99%
“…Akbaraly et al (77) RCT have found that Se supplementation tends to reduce mortality Bjelakovic et al (78) Thyroid effects The iodothyronine deiodinases that produce the active form of thyroid hormone are selenoenzymes, while the antioxidant selenoenzyme GPx is required for the protection of the thyroid from the H 2 O 2 produced there Arthur & Beckett (79) Severe Se deficiency occurs in the endemic goitre belt of north Zaire, which together with iodine deficiency gives rise to myxoedematous cretinism Vanderpas et al (80) An inverse association has been found between Se status and thyroid volume, thyroid tissue damage and goitre in French women Derumeaux et al (81) In RCT in patients with thyroid peroxidase antibodies or autoimmune thyroiditis Se supplementation decreases inflammation and thyroid antibody concentrations and prevents postpartum hypothyroidism Summarised in Rayman (9) GPx, glutathione peroxidise; NHANES III, Third National Health and Nutrition Examination Survey; RCT, randomised controlled trials.…”
Section: Antiviral Effects and Hivmentioning
confidence: 99%
“…However, the authors might not be completely wrong in view of recent reports on harmful effects of atocopherol supplementation. Their findings have recently been supported by a meta-analysis of 68 trials in which the effect of antioxidants (vitamins A, E, C and selenium) was summarized [7]. It was found that a-tocopherol given alone or in combination, significantly increased the mortality when highly biased (low methodology) risk trials were excluded from the calculation.…”
Section: Meta-analyses Of the Intervention Studiesmentioning
confidence: 87%
“…It may be helpful to view the effects of antioxidants generally and the neuroprotective effects of STAZN in particular in this context. Deficiencies in antioxidants, especially in the face of elevated oxidative stress, are deleterious (Shenkin 2006), and yet excessive doses of antioxidant supplementation confer no benefit and, indeed, may be potentially detrimental (Virtamo, Pietinen et al 2003), (Bjelakovic, Nikolova et al 2007). Free radicals and reactive oxygen species themselves, while potentially harmful at levels which overwhelm antioxidant defenses, act as cellular messengers necessary for normal function, and a brief increases may activate protective mechanisms such as are seen in pre-conditioning and post-conditioning (Valko, Leibfritz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…2000;Green and Ashwood 2005). For example, although free radicals and oxidative stress are implicated in most human diseases, a recent meta-analysis of antioxidant supplements, such as vitamin E, vitamin A and β-carotene, found that antioxidant therapy did not confer benefit, but rather increased all-cause mortality in a variety of pathologies including neurological, cardiovascular, ocular, renal, endocrinological, gastrointestinal and dermatological diseases (Bjelakovic, Nikolova et al 2007). Thus, in order to translate the potential of antioxidants to reduce free-radical-mediated damage into clinically significant neuroprotection, a more detailed understanding of the subtleties of antioxidant therapy may be required (Sena, Wheble et al 2007).…”
Section: Introductionmentioning
confidence: 99%